2012
DOI: 10.1097/aln.0b013e318242b2cd
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-induced Neuroapoptosis in the Fetal and Neonatal Rhesus Macaque Brain

Abstract: Background Exposure of rhesus macaque fetuses for 24 h, or neonates for 9 h, to ketamine anesthesia causes neuroapoptosis in the developing brain. The present study further clarifies the minimum exposure required for, and the extent and spatial distribution of, ketamine-induced neuroapoptosis in rhesus fetuses and neonates. Method Ketamine was administered by intravenous infusion for 5 h to postnatal day 6 rhesus neonates, or to pregnant rhesus females at 120 days gestation (full term = 165 days). Three hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
266
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(279 citation statements)
references
References 46 publications
(90 reference statements)
10
266
1
2
Order By: Relevance
“…Brains of both fetal [24] and neonatal rhesus macaques [8,11] display signs of neuronal apoptosis upon exposure to isoflurane (0.7 -1.5 Vol.% for 5 hours). In humans, there is epidemiological evidence to suggest a modestly elevated risk of adverse behavioural or developmental outcomes in children who were exposed to anaesthesia during early childhood [1,3,4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brains of both fetal [24] and neonatal rhesus macaques [8,11] display signs of neuronal apoptosis upon exposure to isoflurane (0.7 -1.5 Vol.% for 5 hours). In humans, there is epidemiological evidence to suggest a modestly elevated risk of adverse behavioural or developmental outcomes in children who were exposed to anaesthesia during early childhood [1,3,4].…”
Section: Resultsmentioning
confidence: 99%
“…benzodiazepines, are known to cause apoptotic death of neurons in the brains of newborn animals [7,8], associated with long-term cognitive deficits [9]. Induction of general anaesthesia in infants mostly involves volatile anaesthetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another patient in that same case series complained of dysphoria after the initial ketamine bolus and asked that drug is discontinued [19]. Due to our study design we are not able to comment on the long term effect of ketamine, more specifically neuroapoptosis, which has been recently raised as major concern and potentially results from the exposure of the developing brain to ketamine [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of studies with conventional animal models have revealed that ketamine can cause neuronal apoptosis during the critical period of the developing brain [7][8][9][10][11][12]. Also a preliminary clinical study indicated that exposure to ketamine over 3 times was detrimental to neurodevelopment in infants [13].…”
Section: Introductionmentioning
confidence: 99%